HUMAN RESOURCE MANAGEMENT AT STIQ AMUNTAI SOUTH KALIMANTAN - Husnawati, Husnawati; Musyarapah, Musyarapah (CV. Lafadz Jaya, 2024)
This research aims to explain human resource management at the STIQ Amuntai, South Kalimantan. The research method used is a qualitative research method with narrative research type. Data collection was carried out by means of depth interview. Data analysis was carried out using the Miles and Hubberman model which consists of data reduction, data display and data verification and drawing conclusions. The research results show that there are several steps taken by STIQ Amuntai in developing human resources consisting of lecturers and education staff, namely by selective employee recruitment with strict selection, participating in regular and scheduled training and development, implementing performance-based management, clear career paths and improve the welfare of lecturers and education staff.